Low-power low-phase noise VCO for 24 ​GHz applications. (March 2020) - Siddique, Abrar; Delwar, Tahesin Samira; Kurbanov, Murod; Ryu, Jee-Youl
Abstract: In this paper, CMOS voltage controlled-oscillator (VCO) with a frequency range of 22.7 ​GHz–27.9 ​GHz is presented. The scheme is modified current-reuse configuration, applicable to 5G applications. In the proposed configuration, the transistors are biased in subthreshold vicinity (VGS ​< ​VTH ) to reduce power consumption. The usage of the capacitive feedback technique helps the output voltage to swing over the positive supply voltage and beneath the potential ground. The inclusion of the cross-coupled NMOS transistors with the inductive source degeneration enhance the transconductance and phase noise performance of VCO. The VCO has been implemented using 65 ​nm CMOS technology. The proposed VCO baised with 0.9 ​V and it showed the lowest power consumption of 1.35 ​mW and the lowest phase noise of −117 ​dBc/Hz at the 1 ​MHz offset frequency as compared to conventional results. This circuit also showed wide tuning range of 26.4%, low FOMT of −194.3 ​dBc/Hz, and small area in core die of 0.35 ​mm ​× ​0.35 ​mm. In addition, we have analyzed the mesaured output power spectrum of the proposed VCO using spectrum analyser (Anritsu, MS2760A) whereas the measured output power of the designed VCO is −7.9 dBm at the frequency of 24.5 ​GHz.